2018
DOI: 10.4103/jrms.jrms_1009_16
|View full text |Cite
|
Sign up to set email alerts
|

Can routine peripheral blood counts like neutrophil-to-lymphocyte ratio be beneficial in prediagnosis of testicular cancer and its stages?

Abstract: Background:The purpose of this study was to assess the diagnostic role of preoperative hematological parameters, especially neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and mean platelet volume (MPV) in germ cell testicular malignancies and their prediagnostic role in staging of testicular cancer.Materials and Methods:In this cross-sectional retrospective study, we analyzed 39 patients who underwent radical orchiectomy due to a testicular cancer (Group 1) and 82 patients on whom va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…In some studies in which the NLR threshold value was investigated, it was found to be 2.25 by Gokcen et al [16], 3.16 by Sahin et al [3] and 2.11 by Ilktac et al [19]. In our study, we have specified the NLR cut-off value as 2.27, which is in accordance with the literature.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In some studies in which the NLR threshold value was investigated, it was found to be 2.25 by Gokcen et al [16], 3.16 by Sahin et al [3] and 2.11 by Ilktac et al [19]. In our study, we have specified the NLR cut-off value as 2.27, which is in accordance with the literature.…”
Section: Discussionsupporting
confidence: 85%
“…In some previous studies, it has been reported that the NLR values were higher in patients with testicular tumors compared to the control group [3,13,16]. Neutrophil/lymphocyte ratios were found to be 3.1±1.4 by Gokcen et al [16], 4.22±3.54 by Sahin et al [3], and 3.18±1.76 by Yuksel et al [13]. In our study, we found that NLR ratio was higher in patients with testicular tumors compared to the control group of similar age group, and this was in accordance with the literature.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Increased neutrophil, platelet and monocyte levels may result from a systemic inflammatory reaction, facilitating cancer progression. Two small studies showed that patients with GCTs have higher NLR and PLR values than healthy controls [ 60 , 61 ]⁠. Recently, high preoperative NLR was identified as a stage predictor and poor prognostic factor for overall survival by two independent groups [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…When the literature is evaluated, it is seen that MPV levels were estimated in genitourinary cancers such as prostate, renal or testicular cancers. Gokcen, et al [27] et al found that MPV was significantly lower in testicular cancer group compared to the healthy group. MPV, NLR and PLR may be helpful for prediagnosis of testicular cancers.…”
Section: Discussionmentioning
confidence: 96%